THE RELATIONSHIP BETWEEN KIE FAMILY PLANNING SERVICES TO INCREASE INTEREST IN BECOMING A FAMILY PLANNING ACCEPTOR IN THE WORKING AREA OF THE LAMPAHAN HEALTH CENTER, TIMANG GAJAH DISTRICT, BENER MERIAH REGENCY, ACEH PROVINCE - Nuraini; Simanjuntak , Rapika Anjani; Eliadona; Panjaitan, Ayu Lestari; Munthe, Juliana (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background The Total Fertility Rate (TFR) in 2010 increased from 2.43 people to 2.60 people. As many as 50.08% of women aged 15-49 years who are accepting birth control, 79.1% of deliveries are assisted by midwives and 92.42% of the child's weight is born alive, which is above 2.5 kg. The number of working population decreased from 7,037 people in 2019 to 6,950 people in 2020. Purpose of Research This research was conducted to determine the relationship between family planning service KIE and interest in becoming a family planning acceptor in the working area of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency, Aceh Province in 2023. Method This research method is observational/survey, namely data collected from respondents using questionnaires or questionnaires without intervening with the research subject. The type of research is descriptive analytical with cross-sectional, which is to connect risk factors with the effects of certain diseases or health statuses. Data analysis of the Majority of KIE Principles on Unclear Family Planning acceptors as many as 20 people (65%) and clear minority as many as 11 people (35%). There is a relationship between KIE and the increase in interest of family planning acceptors seen from the age of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency, Aceh Province in 2023 where the p-value is 0.035 for communication, 0.035 for information and 0.012 for education (p<0.05).